Discrepancy of left and right hip bone mineral density (BMD) in Thai women: Diagnostic agreement and misclassification - Sirianong Namwongprom (2018)
Objective: To determine the diagnostic agreement and the degree of misclassification when using data from the left and right hips. Methods: The cross-sectional study of 1,943 perimenopausal and postmenopausal Thai women, who had bone mineral density (BMD) measurements at the left (non-dominant) and right hips for the screening of low bone mass (LBM) or osteoporosis (OP) in the Department of Radiology, Faculty of Medicine, Chiang Mai University from September 2008 to August 2010 was performed. The kappa statistic was used to assess diagnostic agreement. The prevalence of LBM and OP and the percentage of misclassification were reported. Results: There was a significant correlation between the left and right BMD values for the femoral neck (FN) (r2= 0.83; p < 0.001) and the total hip (TH) (r2= 0.89; p < 0.001). The diagnostic agreement of the FN and TH regions was significant in all study groups ranging from 0.69 to 0.76 (p < 0.001). For the final diagnosis, which is based on the least T-score of the FN or TH regions, the diagnostic agreement was 0.73 for all women, 0.77 for perimenopausal women, 0.73 for postmenopausal women, 0.70 for postmenopausal women age less than 65 years and 0.71 for postmenopausal women age greater than or equal to 65 years. The percentage of misclassification for all women was 16.9 %, with 3.3 % being downgraded from normal to LBM and 3.4 % from LBM to OP. Conclusion: Despite the fact that good diagnostic agreement was demonstrated in this study, a significant number of diagnostic discordance between left and right hips (16.9 %) was also observed. BMD measurements of both hips are recommended for diagnosing LBM and OP in clinical practice. © 2012 The Japanese Society of Nuclear Medicine.